Efficacy and safety of triple diode laser in hair growth reduction - Tayyaba Iqbal; Sadaf Ahmed Asim; Syeda Shamona Tirmizi; Nadia Farooq; Madiha Sajid; Sadia Bhatti (Journal of University Medical & Dental College, 2024)
ABSTRACT Background & Objective: Laser treatment for hair removal is a very common procedure in dermatology. Ruby, diode, alexandrite, Nd yag, and intense pulse light are frequently used for hair reduction. For more effective results a combination of wavelengths is used. The purpose of this study is to determine the efficacy and safety of triple diode lasers in hair growth reduction. Methodology: This interventional longitudinal study comprises of total 82 patients using a non-probability convenience sampling technique, the mean age of the patients was 28.73, the age range was between 17 to 56 years, and all patients in this study were female of skin phenotype between III to V. Each session was done one month apart for four months, and hair growth reduction was assessed by using GAIS (Global Aesthetic Improvement Scale Assessment) score by two independent dermatologists in 4th session. Results: Hair growth reduction was observed in all the enrolled patients from the first session. Out of 82 patients, 63.4% of patients are of skin phenotype IV, 23.2% patients are of skin phenotype III whereas 13.4% are skin phenotype V. After four sessions 41 patients (50%) showed excellent results, and 41 patients (50%) showed good results. None of these patients experienced any long-term side effects. Conclusion: Triple diode laser is a safe and effective modality in hair growth reduction at all body sites in skin phenotype III- V with minimal side effects.